2018
DOI: 10.1097/gox.0000000000001774
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Immediate Breast Reconstruction with Laser-Assisted Indocyanine Green Angiography

Abstract: Background:Complication rates following immediate breast reconstruction range from 4% to 60%. Mastectomy skin flap necrosis (MSFN) is often the sentinel event leading to secondary complications.Methods:All patients undergoing immediate reconstruction were enrolled. Upon mastectomy completion, the surgeon visually interpreted the skin flaps, performed laser-assisted indocyanine green angiography (LAIGA), and intervened if needed. Patients were followed for 90 days, documenting skin necrosis, infection, seroma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 32 publications
(28 reference statements)
1
34
0
Order By: Relevance
“…The individual outcomes of studies are presented in Table . All of the included papers used as an outcome the occurrence of necrosis . One of the included trials did not use infection as an outcome .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The individual outcomes of studies are presented in Table . All of the included papers used as an outcome the occurrence of necrosis . One of the included trials did not use infection as an outcome .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies showed that the use of LAIGA promotes the reduction of necrosis; one of them showed a significant reduction of infection, and three papers showed a significant reduction of necessity for reoperation …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations